Biliary Tract Cancers: Treatment Updates and Future Directions in the Era of Precision Medicine and Immuno-Oncology - Manne, Ashish; Woods, Edward; Tsung, Allan; Mittra, Arjun (Frontiers in Oncology, 2021)
The effective management of biliary tract cancers (BTC) has been hampered by limited options for systemic therapy. In recent years, the focus on precision medicine has made technologies such as next-generation sequencing (NGS) accessible to clinicians to identify targetable mutations in BTCs in tumor-tissue (primarily) as well as blood and to treat them with targeted therapies when possible. It has also expanded our understanding of functional pathways associated with genetic alterations and opened doors for identifying novel targets for treatment. Recent advances in the precision medicine approach allowed us to identify new molecular markers in BTCs, such as epigenetic changes (methylation and histone modification) and non-DNA markers such as messenger RNA, micro RNA, long non-coding RNA. It also made detecting these markers from non-traditional sources such as blood, urine, bile, and cytology (from fine-needle aspiration and biliary brushings) possible. As these tests become more accessible, we can see the integration of different molecular markers from all available sources to aid physicians in diagnosing, assessing prognosis, and predicting tumor response and screening BTCs. Currently, there are a handful of approved targeted therapies and only one class of immunotherapy agents (immune checkpoint inhibitors or ICIs) to treat BTCs. Early success with new targets, vascular endothelial growth factor receptor (VEGFR), HER2, protein kinase receptor, and Dickkopf-1 (DKK1); drugs for known targets, Fibroblast growth factor receptors (FGFRs) such as Futabatinib, Dezaratinib, and Erdafitinib; ICIs such as Durvalumab and Tremelimumab is encouraging. Novel immunotherapy agents such as bi-specific antibodies (Bintrafusp alfa), arginase inhibitors, vaccines, and cellular therapy (Chimeric antigen receptor – T cell or CAR-T, natural killer cells, tumor-infiltrating lymphocytes) have the potential to improve outcomes of BTCs in coming years.